Nanomodified Peek Dental Implants: Bioactive Composites and Surface Modification—A Review - Najeeb, Shariq (Int J Dent, 2015)
Purpose. The aim of this review is to summarize and evaluate the relevant literature regarding the different ways how polyetheretherketone (PEEK) can be modified to overcome its limited bioactivity, and thereby making it suitable as a dental implant material. Study Selection. An electronic literature search was conducted via the PubMed and Google Scholar databases using the keywords “PEEK dental implants,” “nano,” “osseointegration,” “surface treatment,” and “modification.” A total of 16 in vivo and in vitro studies were found suitable to be included in this review. Results. There are many viable methods to increase the bioactivity of PEEK. Most methods focus on increasing the surface roughness, increasing the hydrophilicity and coating osseoconductive materials. Conclusion. There are many ways in which PEEK can be modified at a nanometer level to overcome its limited bioactivity. Melt-blending with bioactive nanoparticles can be used to produce bioactive nanocomposites, while spin-coating, gas plasma etching, electron beam, and plasma-ion immersion implantation can be used to modify the surface of PEEK implants in order to make them more bioactive. However, more animal studies are needed before these implants can be deemed suitable to be used as dental implants.